Efficacy and Safety of Qingfei Paidu Decoction for Treating COVID-19: A Systematic Review and Meta-Analysis - Wang, Qi; Zhu, Hongfei; Li, Mengting; Liu, Yafei; Lai, Honghao; Yang, Qiuyu; Cao, Xiao; Ge, Long (Frontiers in Pharmacology, 2021)
Background: Qingfei Paidu decoction (QFPD) has been widely used in treating COVID-19 in China. However, there is still a lack of comprehensive and systematic evidence on the effectiveness and safety of QFPD. This study aims to evaluate the efficacy and safety of QFPD in patients with COVID-19. Methods: We searched 7 databases up to 5 March 2021. Two reviewers independently screened studies, extracted data of interest, and assessed risk of bias. Cochrane Risk of Bias tool was used to assess the risk of bias of randomized controlled trials. Newcastle-Ottawa Scale was used to assess the risk of bias of cohort and non-randomized trials. The ‘Quality assessment for Before-After (Pre-Post) Studies with No Control Group’ was adopted for controlled pre-post studies. We used the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) to assess the certainty of evidence. We carried out a random effect meta-analysis focusing on efficacy and safety variables. All analyses were conducted by RevMan 5.3. For outcomes that could not be meta-analyzed, we performed a descriptive analysis. Results: We identified sixteen studies with 11237 patients, including one RCT, six non-randomized trials, two cohort studies, and seven pre-post studies. The certainty of evidence was mainly low to very low because of observational study design. QFPD combined with conventional treatment might decrease the time for nucleic acid conversion (MD= -4.78 days, 95%CI: -5.79 to -3.77), shorten the length of hospital stay (MD= -7.95 days, 95%CI: -14.66 to -1.24), shorten the duration of symptoms recovery of fever (MD= -1.51 days, 95%CI: -1.92 to -1.09), cough (MD= -1.64 days, 95%CI: -1.91 to -1.36) and chest CT (MD= -2.23 days, 95%CI: -2.46 to -2.00), improve the overall TCM symptom scores (MD= 41.58 scores, 95%CI: 32.67 to 50.49), and change the laboratory indexes, such as WBC, AST and CRP. Conclusions: QFPD combined with conventional treatment might be more effective for patients with COVID-19. No serious adverse reactions related to the QFPD were observed except mild diarrhea, nausea and vomiting, and hyperhidrotic. More high-quality RCTs are needed in the future.